2016
DOI: 10.1038/srep30144
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of PVDF ultrafiltration membrane fouling by coating MnO2 nanoparticles with ozonation

Abstract: Pre-treatment is normally required to reduce or control the fouling of ultrafiltration (UF) membranes in drinking water treatment process. Current pre-treatment methods, such as coagulation, are only partially effective to prevent long-term fouling. Since biological activities are a major contributor to accumulated fouling, the application of an oxidation/disinfection step can be an effective complement to coagulation. In this study, a novel pre-treatment method has been evaluated at laboratory scale consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Although the FTIR technique is not quantitative, it is reasonable to assume that smaller quantities of residual carbon could be present in the material. All spectra show a very intense drift for  < 580 cm -1 , which is due to the presence of ZnO [31]. Residual graphitic carbon was also confirmed through Raman spectroscopy -as can be seen in Figure S4, the spectrum of the pyrolysed cork shows the characteristic peaks at about 1355 and 1580 cm -1 (D and G peaks respectively) [32].…”
Section: Characterisation Of the Calcined Samplesmentioning
confidence: 71%
“…Although the FTIR technique is not quantitative, it is reasonable to assume that smaller quantities of residual carbon could be present in the material. All spectra show a very intense drift for  < 580 cm -1 , which is due to the presence of ZnO [31]. Residual graphitic carbon was also confirmed through Raman spectroscopy -as can be seen in Figure S4, the spectrum of the pyrolysed cork shows the characteristic peaks at about 1355 and 1580 cm -1 (D and G peaks respectively) [32].…”
Section: Characterisation Of the Calcined Samplesmentioning
confidence: 71%
“…In most cases ceramic membranes have been used in catalytic ozonation systems, because the substrate material is simpler to be coated. However, Yu et al [29] coated a PVDF (polymeric) membrane with MnO 2 nanoparticles. They observed that there was not any detectable additional pressure loss by the presence of coating at the beginning of process operation and the presence of MnO 2 surface layer was found to lower the fouling rate.…”
Section: Fouling Controlmentioning
confidence: 99%
“…In most relevant ozonation cases the ceramic membranes have been commonly applied in the catalytic ozonation systems, because they are fully ozone resistant and the substrate material is simpler to be used as coating substrate. However, Yu et al [23] who have coated a PVDF membrane with MnO 2 nanoparticles; they reported that the presence of these oxide particles lowered the fouling rate and the presence of ozone has limited the bio-accumulation of several components onto the membranes' surface, hence restricting the fouling problem. Furthermore, Sun et al [24] have doped a similar membrane with TiO 2 nanoparticles to examine the removal of nitrobenzene.…”
Section: Catalytic Membrane Contactorsmentioning
confidence: 99%